ANALISIS STRATEGI PONDOK PESANTREN DALAM MENGELOLA WAKTU PEMBELAJARAN SALAF DAN KHALAF - Rahmatul Fajri, Laili; Raisa Farah Diba (Program Studi Manajemen Pendidikan Islam, 2025)
Islamic boarding schools (pondok pesantren) as Islamic educational institutions have two main learning systems, salaf and khalaf, which require effective time management strategies to ensure optimal learning processes. This research is motivated by the importance of balancing the study of classical Islamic texts (salaf) and formal education (khalaf), which directly impacts students’ academic performance and character development. The objectives of this study are: (1) to analyze the strategies of Pondok Pesantren Manarul Huda Pusat in managing the learning schedule of salaf and khalaf, (2) to identify the challenges encountered in the implementation of these strategies, and (3) to evaluate the impact of these strategies on students’ academic achievements and character formation. This research employs a qualitative method with a case study approach and a descriptive design. Data were collected through in-depth interviews, observation, and documentation involving informants such as the boarding school leadership, council of kiai, education section, and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing.The results reveal that time management strategies are carried out through systematic planning, integrated scheduling, and coordination between the boarding school leadership, education section, and the head of the madrasa, while taking into account activity balance and students’ psychological conditions. The main challenges include limited teaching staff, overlapping schedules, students’ discipline issues, and physical as well as mental fatigue. These strategies have proven to positively affect both academic and religious achievements, as well as foster students’ discipline, responsibility, and proper manners.